The Impact of Nonsteroidal Anti-Inflammatory Drugs on the Gastrointestinal Tract and Strategies for Preventing Associated Adverse Effects - Miciuda, Paulina; Bździuch , Patrycja; Cencelewicz , Katarzyna; Buziak , Jakub (Quality in Sport, 2026)
Introduction. Nonsteroidal anti-inflammatory drugs (NSAIDs) are widely used because of their broad range of therapeutic applications. However, their use, regardless of treatment duration, is associated with the risk of adverse effects, predominantly involving the gastrointestinal (GI) tract. Aim. The aim of this paper is to review the potential GI adverse effects associated with NSAIDs and discuss methods for their prevention. Material and methods. The study was prepared based on a review of literature retrieved from the Google Scholar, PubMed, and Scopus databases from recent years. The literature was filtered by keywords: ‘nonsteroidal anti-inflammatory drugs’, ‘gastrointestinal’, ‘upper tract’, ‘adverse effects’, proton pump inhibitor’, ‘small bowel’. Results. NSAIDs-related complications involve both the upper and lower GI tract, however their pathogenesis appears to be distinct. The main mechanism of upper GI tract injury involves weakening of the mucosal barrier and its subsequent damage by gastric acid and digestive enzymes, whereas in case of lower GI tract, studies report the direct harmful effects of NSAIDs on the intestinal mucosa, mitochondrial damage, and alterations in the gut microbiota. Key strategies for the prevention of upper GI side effects involve either co-therapy with NSAIDs and PPIs or selective COX-2 inhibitor use. In contrast, due to a different pathogenesis, probiotics, mucoprotective agents, mesalazine and COX-2 inhibitors used as monotherapy may be beneficial in the treatment and prevention of lower GI complications. Conclusions. Each patient should be individually assessed for complications related to a specific part of the GI tract, with treatment adjusted appropriately.